Physico-chemical characteristics of crosslinked-biofilm made from passiflora edulis waste - Nozieana Khairuddin,; John, Sheena; Suguna Selvakumaran,; Shiamala Ramaiya Devi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In numerous tropical countries, Passiflora Edulis which is also known as passion fruit is grown largely for domestic consumption in both the fresh and processed form. Generally, the sweeter purple passion fruit referred to as the granadilla is preferred for consumption as fresh fruit, while the yellow passion fruit is grown mainly to produce juice concentrate or single-strength juice, fruit preserves, and jams, and as a flavoring agent. Passion fruit peel was used to extract pectin to produce biofilm because of its gelling properties and chemical composition to avoid wastage in the juice industry. The objective of this study is to characterize the physical and chemical properties of the pectinbased biofilm. The films were prepared using a casting technique where pectin acts as biopolymer, starch as the base, and glycerol as the plasticizer. Calcium chloride and citric acid were used as cross-linking agents. The results of the solubility test showed that pectin-based biofilms made from passion fruit are more hydrophilic compared to starch, but there was no significant difference in moisture content between the control and film containing 5 and 7 w/v% of crosslinking agent added. The film formed with calcium chloride showed better physical and chemical properties in terms of thickness, solubility, and moisture content. The formulation based on starch and pectin mixture was less rigid and had better elasticity compared to the control film. Therefore, producing films from passion fruit is a new alternative by taking waste from the juice industry.